Genetic, epigenetic and phenotypic changes in cervical epithelial cells associated with highly oncogenic HPV infection in the process of neoplastic transformation - Sitarz, Katarzyna (2021)
The aim of the study was to detect and analyze morphological and chemical changes related to infection with HPV and the progression of pathological changes and correlation of these alterations with genetic and epigenetic changes, as well as detection of new polymorphisms within the E1 and E2 genes of HPV16 as a prognostic factor for cervical cancer. The studies were carried out with the use of cervical epithelial cells, divided into groups, based on the presence of infection with HPV and the degree of advancement of pathological changes. The research used Raman microscopy and molecular methods. Differences in glycogen and lipid metabolism were found in the tested cells. Glycogen metabolism differed depending on the diameter of the cell nucleus – its level in cells with a large nucleus diameter depended on the presence of HPV infection, while cells with a small nucleus diameter did not show such a relationship. The level of glycogen of the studied groups of cells correlated inversely with the level of lipids. Their highest level was found in cells with the highest advancement of pathological changes. The results were consistent with the results towards the level of methylation of the SREBF1 gene and the level of mtDNA expression. New polymorphisms of the E1 and E2 genes were also discovered, and the relationship between polymorphisms in the E2 gene with neoplasm was demonstrat
Keywords: HPV; cervical cancer; Raman microscopy; DNA methylation; polymorphism